2009
DOI: 10.1097/aln.0b013e3181b27c18
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Electrical Skin Conductance

Abstract: NFSC accurately predicted the absence of moderate to severe pain in postoperative pediatric patients. The measurement of NFSC may therefore provide an additional tool for pain assessment in this group of patients. However, more research is needed to prospectively investigate the observations made in this study and to determine the clinical applicability of the method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(19 citation statements)
references
References 12 publications
6
12
1
Order By: Relevance
“…In fact, they found that the best accordance between a self-reported pain score and SCF per sec occurred in children between the ages of 4 and 8 years. Interestingly, two studies of postoperative pain in children showed that anxiety did not affect the skin conductance analysis (Choo et al, 2010; Hullett et al, 2009) and in one of the studies there was no correlation between skin conductance activity and WBFS scores (Choo et al, 2010), unlike our findings. The lack of correlation between the two procedures may be due to the low specificity of skin conductance to identify moderate pain or it could indicate that WBFS pain scores are influenced by age and health status as shown in our study.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…In fact, they found that the best accordance between a self-reported pain score and SCF per sec occurred in children between the ages of 4 and 8 years. Interestingly, two studies of postoperative pain in children showed that anxiety did not affect the skin conductance analysis (Choo et al, 2010; Hullett et al, 2009) and in one of the studies there was no correlation between skin conductance activity and WBFS scores (Choo et al, 2010), unlike our findings. The lack of correlation between the two procedures may be due to the low specificity of skin conductance to identify moderate pain or it could indicate that WBFS pain scores are influenced by age and health status as shown in our study.…”
Section: Discussioncontrasting
confidence: 95%
“…Our findings using skin conductance monitoring are in line with those reported by Hullet et al (Hullett et al, 2009) who monitored postoperative pain using a postoperative pain score in children. In fact, they found that the best accordance between a self-reported pain score and SCF per sec occurred in children between the ages of 4 and 8 years.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The stimulation strategy used in this study is different from that used in previous studies; we used a more clinically relevant strategy in the form of electrical stimulation of Aβ fibers, which is relatively less painful and noninvasive. Indeed, changes in pulse rate were not observed before or after stimulation (Figure 3) in our study, as compared with previous studies 9,10,19,20. The cold and thermal pain sensations routinely used in pain stimulation experiments are sufficiently severe that heart rate or pulse rate changes are usually observed.…”
Section: Discussionsupporting
confidence: 72%
“…Skin conductance, which measures the electrical conductance of the skin and varies with skin moisture content, has been reported as another independent promising indicator of postoperative pain in children19 and subjects who cannot express their pain. A postoperative study comparing the differences between skin conductance and surgical stress index in pain assessment showed that these parameters could only assess moderate to severe pain with moderate sensitivity and specificity and that their prediction accuracies were similar 5.…”
Section: Discussionmentioning
confidence: 99%